2014
DOI: 10.1158/0008-5472.can-14-2458
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking of T Cells into Tumors

Abstract: T cells are a crucial component of the immune response to infection and cancer. In addition to coordinating immunity in lymphoid tissue, T cells play a vital role at the disease site, which relies on their efficient and specific trafficking capabilities. The process of T-cell trafficking is highly dynamic, involving a series of distinct processes, which include rolling, adhesion, extravasation, and chemotaxis. Trafficking of T cells to the tumor microenvironment is critical for the success of cancer immunother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
282
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(302 citation statements)
references
References 55 publications
2
282
0
2
Order By: Relevance
“…77 This is particularly evident for gliomas, 78 colorectal, 79 breast 80 and cervical cancers. 81 An international consortium is currently prospectively validating this prognostic parameter as an 'immunoscore' for colorectal cancer.…”
Section: T Cell Migration and Entry Into Tumoursmentioning
confidence: 97%
“…77 This is particularly evident for gliomas, 78 colorectal, 79 breast 80 and cervical cancers. 81 An international consortium is currently prospectively validating this prognostic parameter as an 'immunoscore' for colorectal cancer.…”
Section: T Cell Migration and Entry Into Tumoursmentioning
confidence: 97%
“…In fact, improved antitumor responses have been shown to positively correlate with increased cytotoxic T lymphocyte (CTL) infiltration. CTL trafficking is a tightly controlled process, whose homing could be influenced by many factors, such as mismatching of chemokinechemokine receptor pairs, down-regulation of adhesion molecules, and aberrant vasculature (Slaney et al, 2014). CAR-T cell therapy is a personalized treatment involving genetic modification of autologous CTLs, enabling specific recognition and targeting of tumor-associated antigens expressed by the tumor cells or the tumor stroma.…”
Section: T Cell Traffickingmentioning
confidence: 99%
“…Kandalaft et al demonstrated that blocking those receptors improved T cell infiltration into the tumor lesion and enhanced the efficacy of immunotherapy (Kandalaft et al, 2009). Another candidate for enhancing T cell infiltration is VEGF receptor-2, which is overexpressed by tumor-associated endothelial cells (Slaney et al, 2014). Throughout the history of cancer treatment, the long-term therapeutic effect of blocking VEGF receptor-2 has been a major anti-angiogenic pharmacologic intervention and has been fully dependent on CD8 + T cell infiltration in tumors (Manning et al, 2007).…”
Section: T Cell Infiltrationmentioning
confidence: 99%
“…stiffened tissue with high matrix fiber mass and dense collagen network) [113] or the low expression of specific chemokines involved in T-cell recruitment [13,31,114]. Often, the hindrance of lymphocyte infiltration and trafficking is accompanied by the recruitment of suppressive cells and may also be ascribed to abnormal neovasculature derived from VEGF tumor overexpression [21,115,116] and down-modulation by tumor cells of adhesion and chemotactic signals on tumor endothelium, all features found in signatures related to ICB resistance [21,30,117]. Furthermore, CCL2, a chemokine derived from stromal or tumor cells, chemoattracts macrophages and myeloid derived suppressor cells (MDSCs) [118,119], and is highly expressed in ICB-resistant melanoma [21].…”
Section: Tumor-extrinsic Factors Fostering Icb Resistancementioning
confidence: 99%